PENGARUH KOMPENSASI FINANSIAL DAN KOMPENSASI NON-FINANSIAL TERHADAP KEPUASAN KERJA KARYAWAN DI KARANG SETRAHOTEL, SPA & COTTAGES – BANDUNG, JAWA BARAT - Haspul Naser (Sekolah Tinggi Manajemen IMMI Jakarta, 2018)
This research is aim to analyze how the influence of financial compensation and non financial compensation towards job satisfaction in Karang Setra Hotel, Spa Cottages. In collecting the data will use closed questions which is consist of four sections. The first section contains four questions in connection with demography, the second section contains sixteen questions in connection with financial compensation (X1), the third section contains sixteen questions in connection with non financial compensation (X2) and the fourth section contains twenty questions in connection with job satisfaction (Y). It could be concluded and suggested that compensation financial and compensation non-financial have strong enough relationship with job satisfaction. The impact of this research, management karang setra hotel should improve the system of compensation financial and non financial.